Metal–Organic Framework-Based Drug Delivery Systems for Cancer Therapy: A Review - Hatami, Sedigheh (2026)
Cancer remains one of the most significant global health challenges, with conventional treatments limited by side effects and resistance to drugs. The unique properties of metal–organic frameworks (MOFs), which offer high surface areas, tunable structures, and biodegradable properties, make them promising candidates for cancer therapy. This review focuses on MOF-based drug delivery systems for cancer treatment in biomedical applications. This article discusses various synthesis methods, drug-loading strategies, and cytotoxicity considerations. The relationship between the basic chemistry of MOFs and their biomedical applications is elucidated by how each feature directly affects MOF performance in cancer drug delivery. Therefore, this review is a practical and complete guide for researchers working to translate MOFs into effective cancer treatments. Moreover, the role of stimuli-responsive MOFs in cancer therapy is highlighted, along with recent studies demonstrating the effectiveness of MOF-based drug delivery systems. Overall, MOFs offer opportunities for advancing cancer treatment and controlled drug delivery.